PERANCANGAN KENDARAN LISTRIK SEBAGAI ALTERNATIF TRANSPORTASI BERKELANJUTAN DI MASA DEPAN - Brahmantyo Luqman Sayoko; Rafly Mohammad Zidan Hanani Putra; Bagoes Anugrah Pramudiksa (Proceedings Conference On Design Manufacture Engineering And Its Application, 2023)
Awareness of the increasing negative impact of carbon emissions on the environment and the fossil energy crisis has encouraged the development of sustainable transportation alternatives. In this context, electric cars have emerged as a promising solution. This paper aims to present the design and build of an innovative electric car, with a focus on energy efficiency, reliable performance, and reduced carbon emissions. The design is carried out by considering various aspects including light weight, aerodynamic design, power systems, propulsion systems, energy storage systems, and vehicle dimensions. This research involves an analysis of the literature to understand electric vehicle technology and future development trends, while factors such as light weight, aerodynamic design, and long battery life of electric cars are designed to show satisfactory performance. Analysis of the test data revealed higher energy efficiency compared to internal combustion engine (ICE) powered vehicles. In addition, this electric car also shows a significant reduction in carbon emissions, making a positive contribution to global efforts to reduce environmental impact. The results of this study obtained an alternative design and design of electric vehicles, with a length of 2646.36 mm, a width of 1090 mm, a total height of 902.68 mm and a driving motor for the vehicle DB80L048030-ABRUSHLESS DC MOTOR from the Nanotec brand with a voltage of 48 V, rotating maximum of 3300 rpm, ideal speed of 19.2 km/hour, distance of 9.6 km with a time limit of 25 minutes. .The practical goal of this design is a more environmentally friendly and sustainable vehicle alternative to personal transport. It is hoped that this research can spark interest in the development of electric cars and encourage their wider use in the future.